Plasma vitamins and essential trace elements in newly diagnosed pulmonary tuberculosis patients and at different durations of anti-tuberculosis chemotherapy - V.F. Edem; O. Ige; O.G. Arinola (Egyptian Journal of Chest Disease and Tuberculosis, 2015)
Tuberculosis (TB) is a public health challenge worldwide and advancement of latent TB to active disease and drug resistant TB is on the increase as a result of immune suppression induced by Mycobacterium tuberculosis. There are empirical evidences relating immune suppression and malnutrition. To improve the management strategy of TB patients, this study determined micronutrient concentrations in TB patients and established duration (months) post commencement of anti-tuberculosis (anti-TB) chemotherapy that is most important for micronutrient supplementation. Plasma iron, zinc, copper, vitamins A, C, D and E were determined in twenty-four (24) active tuberculosis patients at diagnosis, 2 months, 4 months and 6 months post-commencement of anti-TB chemotherapy, as well as twenty (20) healthy controls. Plasma concentrations of the micronutrients iron, zinc, copper, vitamins A, C, D and E were significantly reduced in TB patients at diagnosis and throughout the period of treatment when compared to controls. Plasma zinc and copper levels were significantly increased at 4 months and 6 months of drug therapy when compared with levels at diagnosis whereas plasma iron was significantly reduced at 4 months of treatment compared with their levels at diagnosis. Vitamins A, C, D and E in TB patients were significantly reduced at 2 months and 4 months of treatment compared to diagnosis. This study concluded that there is micronutrient (Fe, Zn, Cu, Vit A, C, D and E) malnutrition in tuberculosis patients at diagnosis and throughout the duration (6 months) of chemotherapy. Supplementation with vitamins and zinc is advised within the first 4 months of commencing anti-tuberculosis chemotherapy.